Modification of carbonate-activated binder for lead-zinc mine tailings based cemented paste backfill. (4th April 2022) - Wang, Xiangling; Wang, Xiaolei; Shi, Xiaoling
Highlights: CLDH and HM were used to modified carbonate-activated binder for CPB. CLDH and HM strongly modified the binder reaction and phase assembles. CLDH and HM-modified binder showed superior heavy metals immobilization effects. Abstract: CPB promotes a green development of the mining industry. At the same time, the high cost of OPC limits the large-scale application of CPB. This study aimed to use carbonate-activated binders as cementitious materials in LZT based CPB. The binder was modified by CLDH and/or HM when considering the carbonate-activated binder's low reaction rate and bad performance. The effect of 3–5 wt% CLDH and 0.5–1 wt% HM on the reaction kinetics and phase assembles of Na2 CO3 -activated slag was investigated via isothermal calorimetry, XRD, and TG analysis. Flowability, setting time, and compressive strength of CPB samples were used to assess the feasibility of the binder in CPB. The immobilization effect and leaching mechanism of heavy metals from the CPB samples were then evaluated via TCLP, sequential extraction test, and semi-dynamic leaching. The incorporation of CLDH and HM accelerated binder reaction through consuming CO3 2− . The coupling addition of 3 wt% CLDH and 0.5 HM presented the best performance, reaching about 2.29 MPa at 28 days. This value was higher than OPC-based CPB samples by around 10%.